488 TULA for Bladder Tumours in a University Teaching Hospital: Outcomes Over a 2-Year Period. (19th August 2022) - Harrison, N; Bashir, J
Abstract: Aim: TULA (Transurethral laser ablation) of bladder tumours is a relatively non-invasive procedure that is carried out on a day-case basis under local anaesthesia, providing an attractive option for treating recurrent non-muscle invasive bladder cancer (NMIBC). However, data describing efficacy rates are limited. Method: We carried out a retrospective audit of all TULA procedures carried out for bladder lesions between January 2018 and December 2019. Patients were identified using clinical coding and data collected using electronic case note data. Analysis was performed using Microsoft Excel. Results: 48 patients were identified, 75% were male and the average age was 77. Performance status (PS) was formally documented in 6 patients, with a median of 2.5. A total of 77 TULA procedures were identified. 7 patients had TULA as primary treatment, all but one of these patients had significant co-morbidities. Biopsies were taken in 83% of procedures. Recurrence rate at 3 months was 29% (n=14). 18% (n=8) of patients went on to have repeat TULA and the remainder went on to have TURBT or biopsy and cystodiathermy. Of those patients with recurrence, 18% had disease progression. 1 patient required catheterisation and irrigation overnight, all other patients were discharged the same day. No patients required re-admission. Conclusions: TULA is a safe, well tolerated procedure to treat low-grade, recurrent bladder tumours. It can also be used as a palliative procedure for high-grade lesions in patients with multiple co-morbidities. Future work includes collection of objective data on tolerance in the form of VAS pain scoring.